Representações Sociais De Estudantes Do Ensino Médio Da Rede Pública E Particular Sobre A Escola - Carrer, Laercio Da Costa [UNIFESP] (2017)
This research has the theme of schooling process in high school youth. It investigates relationships established with knowledge inside educational institutions. The school environment has become a valued stage of socialization, bringing up some questions. Has the school lost the locus of knowledge? How do the students of public and private schools observe the function of the educational institution in their lives? Will there be differences in the description of students in public and private education regarding the duty of school? The objective of the research is to identify representations about school, for young people in high school in the present time. It aims to recognize similarities or verify differences between students’ narratives in a public school and a private school from São Paulo city, regarding their expectations about school and knowledge.To support for it will be used Pierre Bourdieu (concept of representation) and Phillippe Perrenoud’s (student metier) theoretical references . The data was collected through interviews and questionnaires applied to high school students. It brings concepts about youth, presents historical data about high school identity, and analyzes their role in society. The results demonstrate possibilities to establish convergences and to explain antagonisms about the young people representations in the school universe, marked by the students’ lives objective conditions and their youthful circumstances.